2006
DOI: 10.1088/0031-9155/51/5/022
|View full text |Cite
|
Sign up to set email alerts
|

Magnetogastrographic detection of gastric electrical response activity in humans

Abstract: The detection and characterization of gastric electrical activity has important clinical applications, including the early diagnosis of gastric diseases in humans. In mammals, this phenomenon has two important features: an electrical control activity (ECA) that manifests itself as an electric slow wave (with a frequency of 3 cycles per minute in humans) and an electrical response activity (ERA) that is characterized by spiking potentials during the plateau phase of the ECA. Whereas the ECA has been recorded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 52 publications
(56 reference statements)
0
18
1
Order By: Relevance
“…Artefacts from respiratory and cardiac magnetic interference required us to filter magnetic data. As a result, we did not observe spiking activity reflected in the filtered magnetic signal from these data, although we have seen such activity in previous studies 32,33 Fig. 2Aiii, Biii.…”
Section: Resultscontrasting
confidence: 65%
“…Artefacts from respiratory and cardiac magnetic interference required us to filter magnetic data. As a result, we did not observe spiking activity reflected in the filtered magnetic signal from these data, although we have seen such activity in previous studies 32,33 Fig. 2Aiii, Biii.…”
Section: Resultscontrasting
confidence: 65%
“…Realistic torso models by Kim et.al showed that magnetic fields preserved the information of gastric electrical activity better than potential fields in the change of fat thickness or conductivity (Kim et al , 2012). In addition to the ability to detect gastric slow wave signals with less abdominal volume conductor effect, MGG can detect characteristics of slow wave propagation (Bradshaw et al , 2006), identify uncoupling of the electrical syncytium (Bradshaw et al , 2009b) and distinguish spiking activity (Irimia et al , 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Presumably, injuries of greater severity can be associated with additional significant similarities, and future research should test this hypothesis. For example, the severity of TBI-and AD-related digestive disturbances may be associated with connectomic disruptions which affect similar cortical areas and which may be associated with injury/disease severity [42-45].…”
Section: Discussionmentioning
confidence: 99%